Does Hepatic Steatosis Influence the Virological Response with Chronic Hepatitis B Patients Treated with Entecavir or Tenofovir Disoproxil Fumarate? - Roni Atalay,; Süleyman Sayar,; Fatma Gülçiçek Ayrancı,; Şüheda Çakmak,; İbrahim Halil Tanboğa,; Levent Doğanay,; Kamil Özdil, (Turkish Journal of Gastroenterology, 2022)
Background: The effect of hepatic steatosis on the response to antiviral therapy administered in chronic hepatitis B patients is yet to be clarified. In this study, our aim was to determine the effect of hepatic steatosis on the virological response in chronic hepatitis B patients who were treated with entecavir or tenofovir disoproxil fumarate.Methods: This retrospective cohort study was performed using the data of liver biopsy-proven chronic hepatitis B patients with or without hepatic steatosis, who received entecavir or tenofovir disoproxil fumarate treatment between 2012 and 2017. The undetectable serum hepatitis B virus deoxyribonucleic acid level under treatment was defined as the complete virological response. The predictors of virological response were determined, and it was checked whether the virological response was affected by hepatic steatosis in chronic hepatitis B patients who have undergone entecavir or tenofovir disoproxil fumarate treatment.Results: A total of 324 chronic hepatitis B patients, of which 203 (63%) were males, were included in the study. The median age of the patients was 42 years (range: 35-51 years). Hepatic steatosis was observed in 25% of the patients, and steatohepatitis in 4%. The median time to complete virological response was found to be 6 months (range: 3-9 months). In the full analysis model, the log hepatitis B virus deoxyribonucleic acid was determined as the factor most associated with virological response (P < .001). No statistically signifi- cant relationship was detected between hepatic steatosis and virological response (P = .409).Conclusion: Concomitant hepatic steatosis has no significant impact on the virological response in chronic hepatitis B patients who have undergone entecavir or tenofovir disoproxil fumarate treatment.Cite this article as: Atalay R, Sayar S, Gülçiçek Ayrancı F, et al. Does hepatic steatosis influence the virological response with chronic hepatitis B patients treated with entecavir or tenofovir disoproxil fumarate? Turk J Gastroenterol. 2022;33(7):587-595.